2018
DOI: 10.1111/1747-0080.12498
|View full text |Cite
|
Sign up to set email alerts
|

Development of text messages targeting healthy eating for children in the context of parenting partnerships

Abstract: Aim There has been an increase in the use of text messaging to deliver and support health interventions. The aim was to develop a bank of text messages targeting healthy eating for children in the context of parenting partnerships that could be used in a family intervention. Methods Text messages were developed using the Theoretical Domains Framework and Behaviour Change Wheel COM‐B model by study investigators using a three‐phase approach: (i) initial development of a message bank; (ii) messages were reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…These studies found the COM-B and TDF useful to inform an intervention to promote behaviour. Furthermore, studies have designed dietary interventions based on the COM-B model to promote the Mediterranean diet in adults at risk of CVD (28) , an app to improve eating habits of adolescents and young adults (29) and a text messaging service targeting healthy eating for children in a family intervention (30) . This study investigates the perceived barriers and facilitators to adopting the MIND diet in midlife (40-55 years).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies found the COM-B and TDF useful to inform an intervention to promote behaviour. Furthermore, studies have designed dietary interventions based on the COM-B model to promote the Mediterranean diet in adults at risk of CVD (28) , an app to improve eating habits of adolescents and young adults (29) and a text messaging service targeting healthy eating for children in a family intervention (30) . This study investigates the perceived barriers and facilitators to adopting the MIND diet in midlife (40-55 years).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The COM-B model is an established method for understanding behaviour and used extensively in behaviour change interventions, including dietary studies (30,71) . To our knowledge, this study is the first study to explore barriers and facilitators to adopting the MIND diet, and the first study to use the behaviour change wheel to investigate the MIND diet.…”
Section: Strengthsmentioning
confidence: 99%
“…To advance the field in terms of developing and replicating effective interventions, researchers are encouraged to publish full details of intervention development and content . In this issue, Chai et al detailed the three‐stage development of a bank of text messages targeted to parents of primary school‐aged children, designed to support improvement in child eating behaviours . After evaluation by health experts and parents based on clarity, usefulness and relevance, a bank of 48 text messages were retained for use as a component of a future family‐based nutrition intervention .…”
Section: Developing Intervention Componentsmentioning
confidence: 99%
“…20 In this issue, Chai et al 21 detailed the three-stage development of a bank of text messages targeted to parents of primary school-aged children, designed to support improvement in child eating behaviours. 21 After evaluation by health experts and parents based on clarity, usefulness and relevance, a bank of 48 text messages were retained for use as a component of a future family-based nutrition intervention. 22 Lombard et al 23 previously reported in this journal the protocol for the Communicating Health (CH) study, which focused on using social media for health communication in young adults.…”
Section: Developing Intervention Componentsmentioning
confidence: 99%
“…The increased use of, and reliability of mobile phones has led to a transformation in the way health interventions are delivered. Some examples of interventions delivered via mobile phones include: healthy lifestyle program for young adults [17]; healthy eating for children [18]; and health coaching for weight loss in adults [19]. The Communicating Healthy Beginnings Advice by Telephone Randomised Controlled Trial (CHAT RCT) has harnessed the increased use of mobile phone technology to communicate HB messages via telephone calls (telephone) or text messages (SMS) to pregnant women and women with babies to prevent early childhood obesity [13].…”
Section: Introductionmentioning
confidence: 99%